2019
DOI: 10.3390/biology8020032
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Mitochondrial Toxicity in the Geriatric Population: Challenges and Future Directions

Abstract: Mitochondrial function declines with age, leading to a variety of age-related diseases (metabolic, central nervous system-related, cancer, etc.) and medication usage increases with age due to the increase in diseases. Drug-induced mitochondrial toxicity has been described for many different drug classes and can lead to liver, muscle, kidney and central nervous system injury and, in rare cases, to death. Many of the most prescribed medications in the geriatric population carry mitochondrial liabilities. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 119 publications
1
62
0
Order By: Relevance
“…Most of drug-induced mitochondrial toxicities were not detected in preclinical animal studies. Most of these effects have been proven through studies in isolated cells and mitochondria [33]. Our results showed that Ara-C, and IFOS significantly induce mitochondrial membrane potential collapse in isolated rat neurons, which is consistent with previously published data examining anticancer drugs-induced mitochondrial toxicity in other tissues.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most of drug-induced mitochondrial toxicities were not detected in preclinical animal studies. Most of these effects have been proven through studies in isolated cells and mitochondria [33]. Our results showed that Ara-C, and IFOS significantly induce mitochondrial membrane potential collapse in isolated rat neurons, which is consistent with previously published data examining anticancer drugs-induced mitochondrial toxicity in other tissues.…”
Section: Discussionsupporting
confidence: 92%
“…Mitochondrial toxicity has been identified to cause organ toxicity to the central nervous system, kidney, skeletal muscle, heart and liver [32]. Drug classes identified to cause mitochondrial toxicity are anti-diabetic, cholesterol lowering, anti-depressants, pain medications, certain antibiotics, and anti-cancer drugs [33]. Most of drug-induced mitochondrial toxicities were not detected in preclinical animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…Given the central role of mitochondria in energy metabolism, tissue health and ageing, there is increasing concern regarding the long-term effect that xenobiotics may have on mitochondrial function. Mitochondrial perturbations are likely to increase sensitivity to xenobiotics, decrease cellular repair mechanisms and contribute to both chronic disease states and accelerated ageing (Will et al 2019 ). The most direct method to assess mitochondrial activity is by measuring oxygen consumption rates (OCR).…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence that chemical-induced organ toxicity involves disruption of mitochondrial function more frequently than previously considered (Dykens and Will 2007 ; Will et al 2019 ; Dreier et al 2019 ). Mitochondrial perturbations can have major effects on tissues and organs due to their key role in fatty acid metabolism, energy production and generation of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…However, a gradually increasing intraperitoneal PP dose reduced breast cancer growth without causing death in mice [ 83 ]. Drug-induced mitochondrial toxicity can further lead to liver, muscle, kidney and central nervous system failure [ 84 ].…”
Section: Discussionmentioning
confidence: 99%